The answer is a question : the missing superpower that changes everything and will transform your impact as a manager and leader - Ashley-Timms, Laura; Ashley-Timms, Dominic (TSO (The Stationery Office), 2022)
With ever-increasing workloads, demanding schedules, and growing instability, it's little wonder that our stress levels are rising whilst employee engagement everywhere is miserably low. The world has changed and impacted how we work, yet our management models have not kept pace; we're still trying to manage as we always have-by simply taking on more and more. But what if instead of bringing your problems every day, those you work with started generating the solutions themselves? What if your team could step up and take work off you so that you got 20 percent of your time back? What if making one small change could transform not only your team's engagement levels but also your career? In The Answer Is a Question, multi-award-winning performance consultants Dominic and Laura Ashley-Timms set out a simple approach for rehumanising the practice of management. In a step-by-step walk-through of their ground-breaking STAR® model (used by FTSE and Fortune 500 companies), they'll show how you can develop a new superpower that's been proven to work by the London School of Economics and Political Science (LSE) in a major academic study across sixty-two organisations. This book is produced in stunning full colour and provides invaluable insights, examples, and mini-missions that will show you precisely how to make some immediate changes that will yield fast and exciting results and revolutionise how you manage forever. This isn't another post-pandemic management guide contemplating the nuances of remote work. The Answer is a Question is the distillation of hard-won insights into actionable, measurable steps. The Missing Superpower That Changes Everything And Will Transform Your Impact As A Manager And Leader.